Analisis Usaha Tani Tumpangsari Kubis (Brassicaa Olehraceal) Dan Cabai Merah (Capsicum Annum L) Di Kelompok Tani Ngudi Mulyo Kabupaten Boyolali - Eri Saputra, Mochamad; Mahananto; Prasetyo, Agung; Mutiarra Ridyo, Arum (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
Cabbage and red chilies are the most widely grown vegetables in Boyolali Regency and have a relatively high market demand. Ngudi Mulyo Farmers Group is a farmer group that cultivates cabbage and red chilies using intercropping system. This research aims to determine the economic analysis and feasibility of intercropping cabbage and red chilies. The method of selecting research sites was purposive and the sampling method was by census of 30 farmers. The research analysis methods used are cost analysis, revenue analysis, income analysis, profit analysis, feasibility analysis, breakeven point (BEP), R/C ratio, ?/c ratio, labor productivity. The results of the analysis show that the income of cabbage commodity is higher than that of red chilies when cultivated in intercropping system. Meanwhile, the total income from the intercropping system for the two commodities cabbage and red chili is IDR 45,239,400, with a total cost of IDR 8,329,372.01, so that the income received by farmers by operating the intercropping system is IDR 36,910,027.99. The results of the feasibility analysis based on four indicators of the intercropping system show that intercropping of cabbage and red chilies is feasible.